THE VALUE RELEVANCE OF UNREALISED EARNINGS - Kusuma, Marhaendra; Marjukah, Anis; Kasim, Che Manisah Mohd (Widya Mandala Surabaya Catholic University, 2025)
Research Purposes. To test the relevance of unrealized earnings in financial statements, the impact of implementing fair value accounting on IFRS that has been adopted by countries in Southeast Asia. Research Methods. The object of the study is financial sector companies in Indonesia, Malaysia, Singapore, the Philippines and Thailand, a sample of 156 companies, for the period 2019 – 2022 with observation data of n = 624. Hypothesis testing using multiple linear regression analysis. Research Results and Findings. Unrealized earnings, although income is ephemeral as a result of adjustment to fair value, have value relevance. However, the degree of value relevance depends on the hierarchy of fair value inputs and the possibility of being realized. Unrealized earnings from level 1 inputs and plans to be realized are more predictive and more reacted to by the market than other types. Testing the effect of unrealized earnings based on the hierarchy of fair value inputs and potential to be realized on cumulative abnormal returns as a reflection of market reaction, and on the Altman Z-Score as a reflection of the predictive power of future performance.